(untitled) (Japan, 2012)
This is a photographic web database introducing underwater plants commonly found in coastal areas of Thailand. It is re-edited a same name pictorial, which was published in March 2012. The information was compiled during an international collaborative research between Kasetsart University (KU), King Mongkut's Institute of Technology Ladkrabang (KMITL) and the Japan International Research Center for Agricultural Sciences (JIRCAS).
Keywords: Aquatic plants,Thực vật thủy sinh; Thailand,Thái Lan